Bixa atlantica sp. nov. (Bixaceae), a new species of wild annatto from the Atlantic Forest of eastern Brazil - Antar, Guilherme Medeiros; de Lírio, Elton John; Almeida, Roberto Baptista Pereira; Sano, Paulo Takeo (Phytotaxa, 2022)
Bixa is a Neotropical genus with four to five species recognized and meaningful economic importance due to Bixa orellana, the source of annatto, widely used as a condiment and food coloring. Despite this importance, the genus has had little attention in recent taxonomic studies, and the principal monograph for the genus is outdated and remains unpublished. In the course of the preparation of the treatment of Bixaceae for the Flora of Espírito Santo, Brazil, many specimens identified as Bixa arborea were found, however, they differ from that species in several morphological features, especially in fruit. Instead, these specimens resemble Bixa excelsa; nevertheless, they differ in leaf venation, petal color, fruit color and morphology. These unmatched specimens belong to Bixa atlantica, a new species proposed here, endemic to the Atlantic Forest. Additionally, we provide a distribution map, photograph plates, and phenology graphics for Bixa atlantica and B. excelsa, a preliminary conservation status assessment and comments on the ecology and recognition for the new species.